Complications of the Nonoperative versus Operative Treatment of Displaced and Reduced Distal Radius Fractures in Adults: A Systematic Review - Eva A.K. van Delft; Emilien C.J. Wegenrif; Ralph de Vries; Jefrey Vermeulen; Niels W.L. Schep; Frank W. Bloemers (Journal of Orthopedics, Traumatology and Rehabilitation)
Purpose: Displaced distal radius fractures (DRFs) are treated by reduction and cast immobilization or by reduction and internal fixation. Both treatment options have been extensively researched in the literature, but still there is debate on the favorable treatment. Complications are infrequently described and if present, only mentioned as a minor detail. This study was initiated to provide insight into the rate of complications to add value to the discussion of the optimal treatment. Methods: A comprehensive search was conducted in three bibliographic databases. Suitable studies were randomized controlled trials (RCTs) and retrospective trials that compare reduction followed by cast immobilization or volar plating and reported on complications or suboptimal outcome. Results: Six studies, of which two RCTs and four retrospective studies, were included. In total, 467 patients with a DRF were analyzed. Wound healing problems, hardware-related complications, and removal of hardware occurred solely in patients who were treated by volar plating. Carpal tunnel syndrome, re-displacement, malunion, and severe stiffness occurred more often in the nonoperative group. No difference was found between both treatment options regarding tendon injuries, poor patient-reported outcome, distal radioulnar joint laxity-instability, and persistent pain after 1 year. The intensity of complications and patient-related factors were in general not analyzed in any of the included studies. Conclusion: Based on this systematic review on complications in the treatment of DRFs, there is no evident optimal treatment. The choice of treatment should depend on patient based, shared decision-making, taking the advantages and complications of both the nonoperative and operative treatment into account.